2011
DOI: 10.1603/an11009
|View full text |Cite
|
Sign up to set email alerts
|

Botanophila—EpichloëInteraction in a Wild Grass,Puccinellia distans, Lacks Dependence on the Fly Vector

Abstract: In grass-infecting Epichloë (Ascomycetes: Clavicipitaceae) fungi, the transfer of spermatia for fungal fertilization depends on an insect vector: flies of the genus Botanophila (Diptera: Anthomyiidae). The flies use the fungal stroma, a spore-producing fungal structure surrounding the grass inflorescence, for laying eggs and as a food source for both adults and larvae. This fiy-fungus interaction is generally regarded as obligatory and mutualistic. Two Botanophila taxa were noted among four populations ofthe n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…E. typhina has been recorded in five populations of P. distans, with all growing in anthropogenic habitats (Lembicz and Olejniczak 2009). The association between E. typhina and P. distans has already been investigated in several studies (Czarnoleski et al 2013;Górzyńska et al 2011Górzyńska et al , 2017Lembicz et al 2011Lembicz et al , 2013Olejniczak and Lembicz 2007); we reported a previously unrecorded hyperparasite appearing as dark green spots on E. typhina stromata in 2010 (M. Lembicz and K. Górzyńska, annual report, unpublished).…”
Section: Methodsmentioning
confidence: 67%
“…E. typhina has been recorded in five populations of P. distans, with all growing in anthropogenic habitats (Lembicz and Olejniczak 2009). The association between E. typhina and P. distans has already been investigated in several studies (Czarnoleski et al 2013;Górzyńska et al 2011Górzyńska et al , 2017Lembicz et al 2011Lembicz et al , 2013Olejniczak and Lembicz 2007); we reported a previously unrecorded hyperparasite appearing as dark green spots on E. typhina stromata in 2010 (M. Lembicz and K. Górzyńska, annual report, unpublished).…”
Section: Methodsmentioning
confidence: 67%
“…Here we show that Wolbachia bacteria are indeed present in the Botanophila genus, a relationship not previously recorded. This discovery may help explain the high levels of non-viable Botanophila eggs found in the field (Górzyńska et al 2011;Lembicz et al 2013) since Wolbachia can result in death or improper development of embryos. To confirm this effect of the parasite, further experimentation is required in which adults are cured of the bacterium, allowed to mate, and their progeny assessed.…”
Section: Discussionmentioning
confidence: 92%
“…During past investigations, researchers observed that male Botanophila flies are rare and that a substantial proportion (as much as 30%) of eggs can be non-viable at some sites (Górzyńska et al 2011;Lembicz et al 2013). This could indicate the presence of a sexual parasite in fly populations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are needed to determine whether the associations are mutualistic, parasitic or neutral for one or both partners and whether it is a consequence of coevolution. Recently, new information has emerged that indicate that this fly-fungus interaction is not always a prerequisite for the initiation of the reproductive cycle of the fungus, as previously supposed (Rao & Baumann, 2004;Rao et al, 2005;Górzyńska et al, 2010Górzyńska et al, , 2011.…”
Section: Introductionmentioning
confidence: 95%